Perbedaan Waktu Inkubasi Pupuk Organik Diperkaya untuk Efisiensi Pemupukan Anorganik N dan P pada Tanaman Kedelai: Perbedaan Waktu Inkubasi Pupuk Organik Diperkaya untuk Efisiensi Pemupukan Anorganik N dan P pada Tanaman Kedelai - Vera Oktavia Subardja; Muharam Muharam; Wagyono Wagyono (Universitas Bangka Belitung, 2020)
Fertilization efficiency is an effort to break the chain of inorganic fertilizer use which is increasingly uncontrolled. This study aims to obtain the most appropriate composting time of enriched organic fertilizer to obtain the most optimal crop yield in the context of the efficiency of inorganic fertilizers N and P. The research was carried out in the Soil Fertility Laboratory of the Faculty of Agriculture UNSIKA and the Greenhouse laboratory of PT. Pupuk Kujang Cikampek, held during the dry season of 2017. The research was designed using factorial randomized block design. The first factor was the incubation time of enriched organic fertilizer consisting of 3 levels, namely W1 = 21 days incubation time, W2 = 35 days incubation time and W3 = 49 days incubation time. The second factor is a combination of fertilizing doses consisting of 4 levels, namely P1 = 20 tons of organic fertilizer enriched ha-1 + 100% dose recommended inorganic fertilizer NP, P2 = 20 tons of organic fertilizer enriched ha-1 + 75% dose recommended inorganic NP fertilizer , P3 = 20 tons of organic fertilizer enriched ha-1 + 50% dose recommended inorganic fertilizer NP and P4 = 20 tons of organic fertilizer enriched ha-1 + 25% dose recommended inorganic NP fertilizer. The results showed that the combination of treatment of 21 days after incubation + 25% recommended N and P inorganic fertilizers gave the best results in the total functional microbial population, observed growth and component yields.